Characteristics of Ettawa Crossbred Dairy Goat Rumen Fluid and Digestibility of Palm Oil Industry By-Products - Arief; Jamarun, N.; Satria, B. (Pakistan Journal of Nutrition, 2015)
The in-vitro characteristics of the rumen fluid of ettawa crossbred dairy goats was analyzed to determine the digestibility of range of feeds based on palm oil industry by-products. The research used completely randomized design (CRD) with 5 different ratios of Palm Kernel Cake (PKC) and Palm Oil Sludge (POS) as follows: A; (10% PKC+50% POS), B; (20% PKC+40% POS); C (30% PKC+30% POS; D (40% PKC+20% POS), E; (50% PKC+10% POS). The characteristics of rumen fluid that were measured were pH, Volatile Fatty Acid (VFA) and NH3-N and digestibility of Dry Materials (DDM) and Organic Materials (DOM) in-vitro. The in-vitro study was performed according to the method of Tilley and Terry (1983). The results showed that the measured characteristics of the rumen fluid were within normal limits with pH 6.87-6.94, VFA 102.40-133.62 mM and NH3-N 9:00-9.91 mM. The digestibility of Dry Matter (DDM) ranged from 40.13 to 45.52% and the digestibility of Organic Materials (DOM) ranged from 38.94 to 44.56%. Most of the parameters depended significantly on the ratio of PKC and POS.